2016
DOI: 10.1515/nleng-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soret, Hall and Ion-slip on mixed convection in an electrically conducting Casson fluid in a vertical channel

Abstract: The significance of Soret, Hall and Ion-slip effects on mixed convection flow of an electrically conducting Casson fluid in a vertical channel in the presence of viscous dissipation is analyzed. The system of flow governing equations are converted into the system of non-dimensional equations using appropriate nondimensional transformations and hence solved analytically by homotopy analysis method. A quantitative comparison is made between homotopy analysis method and Adomian decomposition method and the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Shah et al [17] defned the fow of micropolar nanofuid in presence of thermally radiative rotating disks for investigation of mass fux and heat fux. Few more related studies on the said topic can be found from the references [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Shah et al [17] defned the fow of micropolar nanofuid in presence of thermally radiative rotating disks for investigation of mass fux and heat fux. Few more related studies on the said topic can be found from the references [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on the Hall and ion slip properties may be found in the literature. [30][31][32][33][34][35][36][37][38] Heat transfer phenomena become more informative in the field of biological characteristics particularly the analysis of biological tissues, their interaction with heat transfer, and thermodynamic structures of lifeblood. Also, it is more important in procedures such as oxygenation and hemodialysis, and malignancy cure.…”
Section: Introductionmentioning
confidence: 99%
“…Casson uid model is one of the non-Newtonian uids which models uids such as jelly, honey, fruit juices, soup, and blood etc. Casson uid is a shear-thinning uid exhibiting yield stress and which has in nite viscosity at a low shear rate and zero viscosity at the in nity shear rate; RamReddy et al [15] and Amanulla et al [16]. In other words, Casson uid behaves like a solid when yield stress is more than the shear stress but behaves like a liquid and ows when the yield stress is less than the shear stress.…”
Section: Introductionmentioning
confidence: 99%